(untitled) (Damascus University Journal for engineering sciences, 2024)
Although early classical studies demonstrated the presence of an important plastic reserve when catalyzing states of plastic buckling, most practical applications of steel design today still rely heavily on the elastic capacity of buckling. A mathematical and physical debate took place among the great structural scientists in the period between the end of the nineteenth and the beginning of the twentieth about the validity and accuracy of the proposed methods for exploiting plasticity in cases of buckling. This paper discusses the issue of plastic reserve of central compressed column so that plastic reserve relationships of rectangular section can be used to extract plastic reserve for profiled H section under buckling. This research shows that there is an important plastic reserve of the profile section that can be utilized under certain conditions during the occurrence of buckling, and also demonstrates the magnitude of the increase in buckling capacity during the employed the plasticity compared to elasticity. The presence of a reserve of plasticity during buckling shows that there is a possibility of activating a post-buckling state to avoid sudden collapses of instability under seismic loads.